2014
DOI: 10.1063/1.4867117
|View full text |Cite
|
Sign up to set email alerts
|

Vibration interference analysis and verification of micro-fluidic inertial switch

Abstract: The micro-fluidic inertial switch based on liquid metal utilizes the moving mercury droplet to close the switch under the action of acceleration, which is characterized by no moving parts, small contact resistance, long service life and large current. In addition to the requirement of response time, accuracy and reliability, the micro-fluidic inertial switch needs to overcome the impact of the ambient vibration. The influence of the ambient vibration on the performance of switch is investigated by loading puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This microfluidic switch has simple preparation technology and high reliability, but the working temperature range of glycerol is narrow (−17.8 °C-290 °C). Liu et al [86], Yoo et al [5], Li et al [7] also designed micro-fluid inertial switches based on the principle of inertial flow. They used mercury or an ultra-low temperature conductive fluid as working fluids.…”
Section: Passive Inertial Switchesmentioning
confidence: 99%
“…This microfluidic switch has simple preparation technology and high reliability, but the working temperature range of glycerol is narrow (−17.8 °C-290 °C). Liu et al [86], Yoo et al [5], Li et al [7] also designed micro-fluid inertial switches based on the principle of inertial flow. They used mercury or an ultra-low temperature conductive fluid as working fluids.…”
Section: Passive Inertial Switchesmentioning
confidence: 99%
“…The objective threshold acceleration can be configured based on the geometry of the micro-structured channel, the wetting property of the channel surface, and the working fluid. The commonly used working fluids are mercury [57][58][59] and Glycerol [60], which have the advantages of a high surface tension, high density, and electrical conduction. Yoo et al [57] reported that the micro-structured channel can enhance the non-wetting behavior while minimizing the contact angle hysteresis of the micro-droplet on the surface.…”
Section: Persistent Closed Inertial Micro-switchesmentioning
confidence: 99%
“…Park et al [58] fabricated a micro-fluidic switch on a photosensitive glass to uniformly and simultaneously form an anisotropic micro-structured channel during the etching process, providing easy movement of the micro-droplet on the channel surface. Liu et al [59] investigated the influence of the ambient vibration on the performance of the micro-fluidic switch by applying pulse or sinusoidal interference signals in the X, Y, and Z directions. The results suggested that the performance of the switch was greatly affected by the impact interference signal in the sensitive direction as compared with the low frequency harmonic signal.…”
Section: Persistent Closed Inertial Micro-switchesmentioning
confidence: 99%
“…A study of coupled vibration of driving sections for an electromechanical integrated harmonic piezodrive system in the Micro Actuators area 21 and Vibration interference analysis and verification of micro-fluidic inertial switch in the area of Microfluidics and Nanofluidics are shown. 22 For the Bio MEMS and Applications, the efficacy of laser hyperthermia and nanoparticleenhanced therapies by heat shock protein analysis is assessed. 23 And another group of researchers reports a SPR imaging method combined with cyclic voltammetry for the detection of neural activity.…”
mentioning
confidence: 99%